Possibilidade de construção do conhecimento balizada por Freire na alternância pedagógica em um curso de Educação do Campo com habilitação em Ciências da Natureza - Domingos, Diane Cristina Araújo (2024)
The present study presents the possibilities of the understanding the topic of pesticide among graduates of the Natural Science course (2014) and experience reports (RE) of methodological practices of their faculty advisors, from the Indigenous Intercultural Faculty of a public university. The analytical process permeated the Discursive Textual Analysis (ATD), divided into two moments. In the first, discursive information from TCC productions (monograph and articles) anchored in bibliographical research. In the second moment, we investigated the experience reports (RE) of the methodological practices addressed by the teachers based on document analysis. In this way, we elucidated some understandings of the empirical material, which provided an opportunity to understand the importance of minimizing the low level of education of farmers and future rural educators. With this, it even possible to point out pedagogical instruments, such as school/community articulation mediators as a possibility of problematized and dialogical methodology, guided by Freire, based on the pedagogy of alternation, giving new meaning to the construction of scientific knowledge from a perspective of critical consciousness regarding pesticide issues. The role of the rural educator is extremely important in the reproduction of sustainable methodological practices based on Agroecology models, providing knowledge for the licensee to produce, meeting the federal government's food acquisition programs: Food Acquisition Program (PAA) e National School Feeding Program (PNAE), in educational institutions at municipal, state and federal levels. It is also considered that the teaching and learning process of rural educators depends entirely on public policies that regulate AR in Brazil and this has been a struggle since the beginning of humanity. In this way, Degree in Rural Education (LEDUC) reinforces the importance of encouraging emancipatory training, with a critical awareness of socio-environmental, political, economic and cultural issues, unveiling the construction of scientific knowledge to enhance and reconstitute the curriculum, in accordance with the realities and experiences of people of the countryside, the forests and the waters, weaving Freirean pedagogy with the laws and official documents predisposed for Education in/in the Countryside. Finally, this research aims to strengthen the understanding of the counter-hegemonic debate in the Degree in Rural Education (LEDUC) course.